Case Report: Lessons Learned From Subsequent Autologous and Allogeneic Hematopoietic Stem Cell Transplantations in a Pediatric Patient With Relapsing Polychondritis - Veldkamp, Saskia R.; Jansen, Marc H. A.; Swart, Joost F.; Lindemans, Caroline A. (Frontiers in Immunology, 2022)
Background: Autologous hematopoietic stem cell transplantation (autoHSCT) is increasingly being recognized as a treatment option for severe refractory autoimmune diseases (AD). However, efficacy is hampered by high relapse rates. In contrast, allogeneic HSCT (alloHSCT) has high potential to cure AD, but is associated with significant morbidity and mortality, and data in AD are limited. Experience with autologous HSCT in relapsing polychondritis, a rare episodic inflammatory disorder characterized by destruction of cartilage, is scarce and alloHSCT has not been described before. Case presentation: Here, we present a case of a 9-year-old girl who was diagnosed with relapsing polychondritis, with severe airway involvement requiring a tracheostomy. The disease proved to be steroid-dependent and refractory to a wide array of disease-modifying anti-rheumatic drugs and biologicals. After an autoHSCT procedure, the disease became inactive for a short period of time, until the patient experienced a relapse after 31 days, accompanied by repopulation of effector/memory CD8+ T cells. Because of persistent inflammation and serious steroid toxicity, including severe osteoporosis, growth restriction, and excessive weight gain, the patient was offered an alloHSCT. She experienced transient antibody-mediated immune events post-alloHSCT, which subsided after rituximab. She ultimately developed a balanced immune reconstitution and is currently still in long-term disease remission, 8 years after alloHSCT. Conclusion: This case adds to the few existing reports on autoHSCT in relapsing polychondritis and gives new insights in its pathogenesis, with a possible role for CD8+ T cells. Moreover, it is the first report of successful alloHSCT as a treatment for children with this severe autoimmune disease.